2014
DOI: 10.1002/0471140864.ps2708s77
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Translational Modification Profiling—a High‐Content Assay for Identifying Protein Modifications in Mammalian Cellular Systems

Abstract: Protein microarrays are extremely useful for detecting substrates of protein kinases, substrates of ubiquitin ligases and other post translational modifications. The ability to screen binding interactions as well as post-translational modifications of thousands of proteins at once has improved our ability to identify their targets. Utilizing such systems in combination with functional mammalian cell extracts that preserve enzymatic activity offers advantages in identifying semi-quantitative changes of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the next sections, we shall discuss in detail the recently developed PTM profiling approach [30][31][32][33] in the context of specific biological questions related to analysis of the enzymatic machinery and substrates of the ubiquitin system. We shall further illustrate its potential for analyzing the ubiquitin system in the context of cancer research.…”
Section: Methodologies and Approaches Used In Studying The Ubiquitin mentioning
confidence: 99%
“…In the next sections, we shall discuss in detail the recently developed PTM profiling approach [30][31][32][33] in the context of specific biological questions related to analysis of the enzymatic machinery and substrates of the ubiquitin system. We shall further illustrate its potential for analyzing the ubiquitin system in the context of cancer research.…”
Section: Methodologies and Approaches Used In Studying The Ubiquitin mentioning
confidence: 99%
“…In recent attempts to enhance the comprehension of PTMs, protein microarrays have been used as a platform to understand enzymatic reactions in vitro. It has also been used to perform direct studies of protein modifications using cultured cellular extracts surpassing the need to use labour intensive protein purification steps . For instance, Spruck and co‐workers fabricated protein array with around 8000 human recombinant proteins, which can be used to perform “on chip” reaction using either purified enzyme, cell lysates, or biological fluids .…”
Section: Application Of Protein Arrays In Ptm Studiesmentioning
confidence: 99%
“…For example, it has been observed that nearly 60% class PTMs of protein succinylation sites are surrounded or overlapped with protein acetylation sites [8]. These PTMs can also affect the physicochemical properties of proteins, which can provide a mechanism for the dynamic regulation of molecular, self-assembly [9]. The PTMs have been found in the all types of proteins such as the structural proteins, plasma membrane receptors and nuclear transcription factors (Figure 1).…”
mentioning
confidence: 99%